IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI PENGITUNGAN SUARA (SITUNG) DALAM PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019 DI KALIMANTAN TIMUR - Suardi Suardi; Adam Idris; Muhammad Jamal Amin (Jurnal Administrative Reform, 2021)
The results of the study show that the implementation of Situng's policy in the implementation of the 2019 presidential and vice presidential elections in East Kalimantan, in terms of communication, is very intense in carrying out Routine Coordination Meetings in every stage of the 2019 presidential and vice presidential elections. Internal communication, both in the form of guidance technical, coordination meetings, delivery of technical instructions, circulars, monitoring and others as well as communication with external parties as stakeholders are part of communication in implementing the Situng policy, then in terms of resources, operator readiness is of particular concern, such as the introduction and training for Situng operators as users in operating Situng. The readiness of the Situng supporting equipment itself includes budget allocations in its implementation that already exist, in terms of the attitude going well, this is proven in the 2019 Election in East Kalimantan Province both in Bontang City, West Kutai Regency and Paser Regency, there are no stages that are delayed or the existence of a re-voting, then in terms of the bureaucratic structure within the KPU institution is binding in this case the RI KPU carries out its duties and obligations in terms of making policies in the form of a KPU Regulation (PKPU) so that it is binding and also becomes a guideline for the provincial KPU as regional coordinator and Regency and City KPU as executor. The inhibiting factor for the implementation of the Situng policy is that the determination of Situng operators is constrained by the number of human resources which can only be taken from the technical implementation division. Suggestions in this study are that it is necessary to socialize changes in regulations at every level of communication with external parties as stakeholders, so that the purpose of using the application can be understood together, it takes understanding to KPPS regarding writing in the minutes of recapitulation results at the KPPS level, conducting special recruitment of supporting staff to support the implementation of Situng, which of course will be placed as a Scan, Entry, and Verifier operator.Keyword : Situng Implementation, East Kalimantan 2019 Election